2005
DOI: 10.1007/s10531-004-0537-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of microsatellite variability and population genetic structure of two endangered wild rice species, Oryza rufipogon and O. officinalis, and their conservation implications

Abstract: Conserving endangered wild rice species requires a thorough understanding of their population genetic structure and appropriate approaches. We applied six and seven microsatellite loci to study the genetic structure of six populations throughout the range of Chinese Oryza rufipogon and Oryza officinalis, respectively. The results showed that O. rufipogon possesses higher levels of genetic diversity but lower differentiation (R S ¼ 3.2713, P ¼ 100.0%,Mean population F IS was slightly larger for O. officinalis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
(61 reference statements)
0
10
1
Order By: Relevance
“…More than two thousands microsatellite loci isolated from the genome of O. sativa (e.g., Akagi et al 1996;McCouch et al 1997;Cho et al 2000;Temnykh et al 2000) have provided promising opportunities to study genetic diversity and population structure of rice species (e.g., Gao et al 2002a;Song et al 2003;Gao 2004;Gao and Zhang 2005). In this study, we used 19 microsatellites to assess the genetic variation within 92 accessions of O. rufipogon preserved in two field gene banks.…”
Section: Introductionmentioning
confidence: 99%
“…More than two thousands microsatellite loci isolated from the genome of O. sativa (e.g., Akagi et al 1996;McCouch et al 1997;Cho et al 2000;Temnykh et al 2000) have provided promising opportunities to study genetic diversity and population structure of rice species (e.g., Gao et al 2002a;Song et al 2003;Gao 2004;Gao and Zhang 2005). In this study, we used 19 microsatellites to assess the genetic variation within 92 accessions of O. rufipogon preserved in two field gene banks.…”
Section: Introductionmentioning
confidence: 99%
“…Similar issues are raised with concerns of drug and vaccine resistance for human health, where the spatial variation in drug or vaccine use could influence the evolution of the pathogens being controlled (McLean 1995;Heinemann 1999;Gandon et al 2001). The importance of spatial variation in selective pressures for conservation genetic programs is somewhat different (Robert et al 2003;Gao and Zhang 2005;Jamieson et al 2006;Bohme et al 2007). Here, the goal is to maintain or increase genetic diversity within a population.…”
Section: Discussionmentioning
confidence: 96%
“…These issues can be of direct practical concern. For example, conservation genetics often aims to maximize the genetic diversity of endangered populations (Robert et al 2003;Gao and Zhang 2005;Jamieson et al 2006;Bohme et al 2007), and health or agricultural programs aim to minimize the fixation probability of alleles for insecticide, drug, or vaccine resistance (McLean 1995;Heinemann 1999;Scott et al 2000).…”
mentioning
confidence: 99%
“…Despite many SSR studies on the cultivated rice and its closely related wild species Ishii et al, 2000;Gao et al, 2002;Zhou et al, 2003;Garris et al, 2005), relatively few studies have been undertaken on the population genetics of the B-and C-genome species using SSRs (Gao and Zhang, 2005). Of the four diploid species in this study, O. officinalis maintained the highest diversity (P-71.4%, A=2.71, He-0.565), folk)wed by O. eichingeri (P=57.1%, A=1.71, He=0.376), O. punctata (P=57.1%, A=2.14, He=0.272) and O. rhizomatis (P=42.9%, A=1.43, He=0.222) ( Table 2).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…For example, Zhou et al (2003) revealed much higher level of genetic diversity in the Chinese populations of the Agenome O. rufipogon using 10 SSR primers (P-100%, A=10.6, He=0.787). Recently, Gao and Zhang (2005) applied six and seven SSR loci to investigate the genetic structure of six populations throughout the range of the Chinese O. rufipogon and O. officinalis, respectively. They found that O. rufipogon possessed higher levels of genetic diversity (P=100%, He=0.580) than O. officinalis (P=57.1%, He=0.283).…”
Section: Genetic Diversitymentioning
confidence: 99%